Arabidopsis O‐GlcNAc transferase SEC activates histone methyltransferase ATX1 to regulate flowering. (27th August 2018) - Xing, Lijing; Liu, Yan; Xu, Shujuan; Xiao, Jun; Wang, Bo; Deng, Hanwen; Lu, Zhuang; Xu, Yunyuan; Chong, Kang
Abstract: Post‐translational modification of proteins by O ‐linked β‐ N ‐acetylglucosamine ( O ‐GlcNAc) is catalyzed by O ‐GlcNAc transferases (OGTs). O ‐GlcNAc modification of proteins regulates multiple important biological processes in metazoans. However, whether protein O ‐GlcNAcylation is involved in epigenetic processes during plant development is largely unknown. Here, we show that loss of function of SECRET AGENT (SEC), an OGT in Arabidopsis, leads to an early flowering phenotype. This results from reduced histone H3 lysine 4 trimethylation (H3K4me3) of FLOWERING LOCUS C ( FLC ) locus, which encodes a key negative regulator of flowering. SEC activates ARABIDOPSIS HOMOLOG OF TRITHORAX1 (ATX1), a histone lysine methyltransferase (HKMT), through O ‐GlcNAc modification to augment ATX1‐mediated H3K4me3 histone modification at FLC locus. SEC transfers an O ‐GlcNAc group on Ser947 of ATX1,  which resides in the SET domain, thereby activating ATX1. Taken together, these results uncover a novel post‐translational O ‐GlcNAc modification‐mediated mechanism for regulation of HKMT activity and establish the function of O ‐GlcNAc signaling in epigenetic processes in plants. Synopsis: The Arabidopsis O ‐GlcNAc transferase SECRET AGENT (SEC) activates histone methyltransferase ARABIDOPSIS HOMOLOG OF TRITHORAX1 (ATX1) by O ‐GlcNAc modification, thereby instructing epigenetic modifications required for timely flowering. Arabidopsis mutant for O ‐GlcNAc transferase SEC exhibits an early flowering phenotype. Histone methyltransferase ATX1 is a substrate of SEC. SEC activates ATX1 through O ‐GlcNAcylation at serine 947. ATX1 epigenetically upregulates transcription of FLC, an inhibitor of flowering. Abstract : Post‐translational regulation of a trithorax‐family methyltransferase by O ‐glycosylation reveals the involvement of O ‐GlcNAc signaling in epigenetic processes in plants.